Studi Etnobotani pada Masyarakat Suku Jawa dalam Memanfaatkan Tumbuhan Obat di Desa Sumber Makmur - Hastiana, Yetty; Saputri, Wulandari; Apryyanty, Desy (UNIVERSITAS PGRI MADIUN, 2023)
The use of medicinal plants is carried out by the community in Sumber Makmur Village from generation to generation which is conveyed orally, therefore it is necessary to document the use of medicinal plants by the Javanese tribal community through ethnobotany studies. This study uses descriptive methods with qualitative and quantitative approaches. This type of research is a case study research type. The subjects in this study were the people of Sumber Makmur Village with a sample limit of 50 informants to be interviewed. This study uses 2 types of data sources, namely primary and secondary data. Data were collected through observation, interviews and documentation. Qualitative data were analyzed in 3 stages, namely reduction, data presentation and drawing conclusions, while quantitative data were analyzed using the ICS formula. The results of the research show that there are 36 types of medicinal plants which are grouped into 23 families, with the most plant species from the Zingiberaceae family, namely 8 plant species. The most widely used part of the plant is the leaf. Medicinal plants can be processed in several ways, namely boiled, grated, mashed, dried, brewed and burned by means of usage, namely drinking, dripping, smeared and used for bathing. The calculation of the culturally important value index shows that there are 6 plant species that fall into the medium category with the highest value being 30 and 7 plant species belonging to the low category with the smallest value being 6.